Effects of ultra-high pressure on effective synthesis of fructooligosaccharides and fructotransferase activity using Pectinex Ultra SP-L and inulinase from Aspergillus niger. Issue 7 (9th August 2019) - Kawee-Ai, Arthitaya; Chaisuwan, Worraprat; Manassa, Apisit; Seesuriyachan, Phisit
Abstract: In this study, various levels of ultra-high pressure (UHP) were combined with the enzymatic synthesis of the fructooligosaccharide (FOS) using Pectinex Ultra SP-L and inulinase. The combination enhanced the FOS yields up to 2.5- and 1.5-fold, respectively, compared to atmospheric condition (0.1 MPa). However, the enzymatic reaction was dependent on the levels of pressure, the reaction times, and the initial sucrose concentrations. The combined UHP and inulinase showed that the maximum FOS yield (71.81%) was obtained under UHP at 200 MPa for 20 min with 300 g/L of initial sucrose as a substrate, while the FOS yield (57.13%) using Pectinex Ultra SP-L was obtained under UHP at 300 MPa for 15 min with 600 g/L of initial sucrose as a substrate. The FOS composition produced by Pectinex Ultra SP-L under the UHP was 1-kestose (GF2 ), nystose (GF3 ), and 1F-fructofuranosylnystose (GF4 ), whereas the FOS produced by inulinase composed of only GF2 and GF3 . The combined UHP is a useful tool in the industrial application for FOS production. Highlights: UHP activated the activity of Pectinex Ultra SP-L yet inactivated inulinase Pressure level, time, and sucrose concentration significantly affect FOS yields under UHP UHP enhanced FOS production with time-saving benefits within 15–20 min